2017
DOI: 10.1213/ane.0000000000001814
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Pharmacologic Pre- and Postconditioning With Sevoflurane Compared With Total Intravenous Anesthesia in Liver Surgery: A Cost Analysis

Abstract: Published ahead of print January 5, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This implies for most patients a stay on an intermediate care or an ICU with increased costs, as shown in a study after abdominal surgery from Wang et al 33 Previous studies have demonstrated that lower complication rates reduce health care costs. 34…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies for most patients a stay on an intermediate care or an ICU with increased costs, as shown in a study after abdominal surgery from Wang et al 33 Previous studies have demonstrated that lower complication rates reduce health care costs. 34…”
Section: Discussionmentioning
confidence: 99%
“…This implies for most patients a stay on an intermediate care or an ICU with increased costs, as shown in a study after abdominal surgery from Wang et al 33 Previous studies have demonstrated that lower complication rates reduce health care costs. 34 The question remains, how patients with increased IL-6 plasma levels in the perioperative phase should be addressed. One approach could be a focused antiinflammatory treatment, although this may be symptomatic intervention only.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical trials showed that volatile anesthetic preconditioning in liver surgery had a protective effect [36,37], and recent work suggested that one of the most important protective mechanisms of anesthetic preconditioning is inhibition of inflammation. It was reported that desflurane inhalation reduced endotoxin-induced cytokine responses, decreasing expression of TNF-α and IL-1β [38].…”
Section: Discussionmentioning
confidence: 99%
“…The hospital length of stay (LOS) and overall complications were also significantly reduced with both protective strategies compared to the control group. A cost analysis based on these two RCTs [60] later suggested a reduction of hospital costs with pre-and postconditioning compared with the control group, however, without reaching statistical significance.…”
Section: Liver Resectionsmentioning
confidence: 99%